A NEEDS ANALYSIS OF MATHEMATICS TEACHER LITERACY MENTORING TO ENHANCE STUDENTS' HIGHER-ORDER THINKING SKILLS (HOTS) - Nita Putri Utami; Resva Ingriza; Nana Sepriyanti; Amania Khairul (UIN Imam Bonjol Padang, 2026)
The demands of the 21st century require teachers to possess mathematical literacy, information technology proficiency, and Higher-Order Thinking Skills (HOTS). This study aims to analyze the needs for mathematics teacher literacy mentoring in an effort to enhance students' HOTS within the Mathematics Teachers’ Working Group (MGMP) of Senior High Schools in Pesisir Selatan Regency. The study employed a descriptive quantitative research design. Data were collected using a questionnaire distributed to mathematics teachers, while percentage analysis was used to identify the distribution of responses and mentoring needs. The findings revealed that the aspect of mathematical literacy requiring the greatest mentoring support was conceptual understanding of mathematics, with a percentage of 76.7%. Furthermore, in supporting the improvement of students' HOTS, the learning component most in need of development assistance was HOTS-based teaching modules, with a percentage of 53.3%. These findings indicate that teachers still require capacity-building support in integrating mathematical literacy into HOTS-oriented learning. Therefore, appropriate strategies are needed to strengthen teachers' conceptual understanding and their ability to develop HOTS-based instructional materials, thereby making the learning process more effective in enhancing students' higher-order thinking skills.